Fundamentals of English grammar chartbook: a reference grammar - Azar, Betty Schrampfer (Longman, 2003)
The "Azar Grammar Series" offers concise, level-appropriate grammar presentation with a variety of written exercises and communicative classroom activities. Included are both student-centred pair and group work.